Participative Management Practices and Institutional Goal Attainment in Nigerian Universities - Omorobi, Garieth Omorobi; Mbon, Usen Friday; Owan, Valentine Joseph; Ekpenyong, John Asuquo (American Journal of Social Sciences and Humanities, 2020)
This study evaluated the relationship between participative management practices and institutional goal attainment among Nigerian universities, with University of Calabar in focus. To achieve the purpose of the study, two research questions and two null hypotheses where developed to guide the study. The descriptive survey research design was adopted for the study. The population and sample of the study was one hundred and twenty-two (122) deans of faculties and heads of departments using the census approach. An instrument titled Participative Management Practices and Institutional Goal Attainment Questionnaire (PMPIGAQ) was used for data collection. The instrument was validated by three experts in Higher Education Administration and Measurement and Evaluation. The instrument yielded Cronbach’s reliability alpha ranging from α=.75-86. Data were collected and analyzed through mean, Standard deviation, Pearson Product Moment Correlation Analysis. The results of the study showed that there is a significant relationship between participation in decision making, participation in planning and institutional goal attainment. It was recommended that managers of universities should promote participatory management practices to enhance high morale, commitment and enthusiasm among staff in the pursuit and attainment of institutional goals.